Carbonated hydroxyapatite inflammation’s responses on local rabbits: study of neutrophils’s cell count, macrophages, and edema volumes on mandible - Aryan Morita (Biomedical Engineering, 2015)
Objective: The aims of this study was to find out the response of tissue inflammation implanted CHA thanstandard HA through the amount of neutrophil, macrophage, and edema volumes.Methods. Sixty local rabbits divided into 3 groups that contain 20 rabbits. Each group divided into 5 sub groupsthat observed in day-1, 3, 5, 7, and 14. On first day, all rabbits were anesthesized and incised to create cavity inthe mandible. CHA or HA powder as much as 0,05 g were put into it. Then it was sutured using silk thread. Onthe designated day, the mandibles of 4 rabbits from each sub group were decapitated. The mandibles were fixedwith 10% formalin in PBS pH 7,4. Von Ebner method for decalcification were used followed by hematoxylin eosinstaining to examine neutrophil and macrophage.Results: The number of neutrophil, macrophage, and edema volumes in CHA implantation were lower thanHA. There were not any significant difference (p>0,05) between CHA, HA, and without CHA or HA.Conclusion: There are no differences inflammation respons in CHA implantation and HA.